Manufacturing and properties of a magnesium interpenetrating phase composite - Steinacher, Matej (Strojniški vestnik, 2016)
The manufacturing and properties of the AE44 magnesium alloy reinforced with SiC-Al2O3-SiO2 ceramic foam were studied. The interpenetrating phase composite was manufactured by gravity casting at different preheating temperatures of the ceramic foam. The samples were investigated using optical and electron microscopy, energy dispersive X-ray spectroscopy, X-ray diffraction, transmission electron microscopy and compression testing. The interfacial reaction products (AlSiRE and AlMgSiRE) between the metal phase and ceramics were influenced by the preheating temperatures of ceramic foam and reduced the compression strength significantly.
Keywords: gravitacijsko kokilno litje; keramična pena; kompozit z infiltrirano kovinsko osnovo; magnezijeva zlitina AE44; mehanske lastnosti; reakcijski produkti